2017
DOI: 10.1007/s11427-017-9020-1
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic constrains on mycorrhizal specificity in eight Dendrobium (Orchidaceae) species

Abstract: Plant phylogeny constrains orchid mycorrhizal (OrM) fungal community composition in some orchids. Here, we investigated the structures of the OrM fungal communities of eight Dendrobium species in one niche to determine whether similarities in the OrM fungal communities correlated with the phylogeny of the host plants and whether the Dendrobium-OrM fungal interactions are phylogenetically conserved. A phylogeny based on DNA data was constructed for the eight coexisting Dendrobium species, and the OrM fungal com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 49 publications
5
31
1
Order By: Relevance
“…Because the three life forms represent largely different environments, they may select for different mycorrhizal fungi. Our results showed that members of the Tulasnellaceae were the most dominant fungi in the three life forms, supporting previous findings that Tulasnellaceae symbionts are ubiquitous in terrestrial orchids worldwide (Jacquemyn et al 2017) as well as in some epiphytic orchids (Kartzinel et al 2013, Xing et al 2017. Besides members of the Tulasnellaceae, other rhizoctonia fungi of the Ceratobasidiaceae and Sebacinales (Dearnaley et al 2012) were observed, particularly in terrestrial and epiphytic orchids, but not in the lithophytic species, which almost exclusively associated with fungi from the Tulasnellaceae.…”
Section: Host Specificity and Selectivity In Terrestrial Epiphytic Asupporting
confidence: 89%
See 3 more Smart Citations
“…Because the three life forms represent largely different environments, they may select for different mycorrhizal fungi. Our results showed that members of the Tulasnellaceae were the most dominant fungi in the three life forms, supporting previous findings that Tulasnellaceae symbionts are ubiquitous in terrestrial orchids worldwide (Jacquemyn et al 2017) as well as in some epiphytic orchids (Kartzinel et al 2013, Xing et al 2017. Besides members of the Tulasnellaceae, other rhizoctonia fungi of the Ceratobasidiaceae and Sebacinales (Dearnaley et al 2012) were observed, particularly in terrestrial and epiphytic orchids, but not in the lithophytic species, which almost exclusively associated with fungi from the Tulasnellaceae.…”
Section: Host Specificity and Selectivity In Terrestrial Epiphytic Asupporting
confidence: 89%
“…Ninety-six clones were randomly selected from each library and sequenced using the M13 forward primer. Our previous studies have shown that this was a large enough clonal pool for assessing total species diversity and sequencing completeness (Xing et al 2015(Xing et al , 2017. All clones were sequenced by GENEWIZ Inc., Beijing, China.…”
Section: Assessment Of Mycorrhizal Communitiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The occurrence and geographical variation in local abundance of fungal strains can be influenced by local habitat conditions (Pandey, Sharma, Taylor, & Yadon, ) and OMF community composition may therefore be the result of complex interactions between different factors, including extrinsic factors (habitat type, geographical site, soil characteristics, etc.) and intrinsic factors (genetic differentiation, phylogeny of host plants; Chen et al, ; McCormick & Jacquemyn, ; Swarts & Dixon, ; Xing, Ma, Men, Chen, & Guo, ). Previous research has, for example, shown that variation in local environmental factors such as soil moisture content, pH, nutrient conditions (especially soil carbon, nitrogen and phosphorus) can generate pronounced differences in mycorrhizal communities (Bunch, Cowden, Wurzburger, & Shefferson, ; Jacquemyn et al, ).…”
Section: Discussionmentioning
confidence: 99%